1997
DOI: 10.1161/01.cir.96.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Chlamydia pneumoniae Antibodies, Cardiovascular Events, and Azithromycin in Male Survivors of Myocardial Infarction

Abstract: An increased anti-Cp antibody titre may be a predictor for further adverse cardiovascular events in post-MI patients. Taking a short course of azithromycin may lower this risk, possibly by acting against Cp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
311
6
22

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(346 citation statements)
references
References 17 publications
7
311
6
22
Order By: Relevance
“…In agreement with our finding in EH, clinically significant associations with high levels of IgG antibodies to C. pneumoniae, but not with C. pneumoniae infection in which the levels of these antibodies are low, have been described in other cardiovascular diseases. [18][19][20] On the basis of these results, Neumann et al 18 who analysed the frequency of restenosis after coronary stenting in relation with the titer of IgG antibodies to C. pneumoniae, suggested that it is not the C. pneumoniae infection as such but the variable host response to infection that affects the clinical end point. We do not know whether the above-mentioned high levels of sIgGa-Cp in our population are the consequence of characteristics of the host response to infection or are the consequence of pathogen peculiarities.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our finding in EH, clinically significant associations with high levels of IgG antibodies to C. pneumoniae, but not with C. pneumoniae infection in which the levels of these antibodies are low, have been described in other cardiovascular diseases. [18][19][20] On the basis of these results, Neumann et al 18 who analysed the frequency of restenosis after coronary stenting in relation with the titer of IgG antibodies to C. pneumoniae, suggested that it is not the C. pneumoniae infection as such but the variable host response to infection that affects the clinical end point. We do not know whether the above-mentioned high levels of sIgGa-Cp in our population are the consequence of characteristics of the host response to infection or are the consequence of pathogen peculiarities.…”
Section: Discussionmentioning
confidence: 99%
“…When the animals were treated with macrolides, however, these lesions did not develop 26 . Preliminary clinical randomized trials 27,28 that still await confirmation support a causal relation between Chlamydia pneumoniae and coronary artery disease.…”
Section: Original Articlementioning
confidence: 99%
“…En 1994, une autre série annonçait une association entre maladie coronaire et infection par Helicobacter pylori [6]. Publiés en 1997, deux essais cliniques pilotes [7,8] ont suggéré qu'un traitement antibiotique par macrolide améliore le pronostic de la maladie coronaire. Malgré leurs imperfections, ils ont grandement stimulé l'intérêt pour l'hypothèse infectieuse de l'athérosclérose, car ils faisaient miroiter ses potentialités thérapeutiques.…”
Section: Historique De L'hypothèse Infectieuseunclassified
“…: données incertaines ; ±: données contradictoires ; + à +++: arguments probants, de force croissante. [7,[26][27][28]. L'enthousiasme éveillé par les deux premières publications [7,8] mérite à présent d'être sérieusement modéré.…”
Section: Modèles Expérimentauxunclassified
See 1 more Smart Citation